Application Of The Porous Plug System In The Anode Furnace At Onsan Smelter (2003) - Sang-Su Lee (The Minerals, Metals and Materials Society, 2003)
This paper shows the application of the porous plug system in the Mitsubishi continuous copper smelting and converting process. This system has already been adopted and utilized in the steel industry to enhance productivity. Recently, some copper smelters have adopted this system but the results have not been satisfactory. The porous plug system was installed at the anode furnace in December 2001 to reduce the oxidation time and decrease the oil consumption. A good effect was that the nitrogen stirring of the melt through porous plugs improved the melt heat transfer. As the result of the enhancing heat transfer the oil consumption and the build-up inside the furnace were actually decreased. But until now the oxidation time has not been sufficiently reduced. In the future, further research and tests are needed in order to increase the productivity and save costs.